Enhancing seismic performance of tension-only concentrically braced beam-through frames through implementation of rocking cores. (15th August 2018) - Hu, Shuling; Wang, Wei; Qu, Bing
Highlights: The rocking core can reduce the maximum inter-story drift ratio in a BTF. The rocking core can create a uniform inter-story drift ratio distribution in a BTF. A simple approach is established to locate the soft story in a BTF. A unified seismic performance measure is established. Abstract: Beam-through concentrically braced frames consisting of tension-only braces (denoted as BTFs) have been progressively used as lateral force resisting systems in low-rise and mid-rise buildings in regions with seismicity. However, recent experimental and analytical investigations showed that the code-compliant BTF system may be vulnerable to the failure caused by the excessive inter-story drift ratio at a certain story (which is defined as the ratio of the inter-story drift to the height of the story) due to formation of the soft-story mechanism. This paper investigates the adequacy of the rocking core technology for mitigating such failures in the code-compliant BTFs. First, this paper discusses how the rocking core technology can be implemented in BTFs. Then, this paper presents a method to identify the soft story in a given BTF. Next, through parametric Nonlinear Response History Analyses (NRHA) of four representative benchmark BTF buildings, this paper investigates the validity of the rocking core technology in enhancing seismic performance of BTFs. Specifically, the influences of rocking core stiffness on the maximum inter-story drift ratio response and uniformity of the inter-story drift ratio distribution in each of the benchmark BTF buildings are quantitatively addressed based on the result database gleaned from the NRHA. Moreover, this paper establishes a seismic performance measure which considers both the maximum inter-story drift ratio response and uniformity of the inter-story drift ratio distribution. The seismic performance measure was used to interpret how the rocking core technology improves seismic performances of the demonstration buildings. Results from this research demonstrate that the rocking core technology can reduce the maximum inter-story drift ratio response while improving uniformity of the inter-story drift ratio distribution in BTFs. Also presented in the paper are some design recommendations for the rocking cores implemented in the BTFs based on the NRHA results.